The Campylobacter jejuni Oxidative Stress Regulator RrpB Is Associated with a Genomic Hypervariable Region and Altered Oxidative Stress Resistance - Gundogdu, Ozan; da Silva, Daiani T.; Mohammad, Banaz; Elmi, Abdi; Wren, Brendan W.; van Vliet, Arnoud H. M.; Dorrell, Nick (Frontiers in Microbiology, 2016)
Campylobacter jejuni is the leading cause of bacterial foodborne diarrhoeal disease worldwide. Despite the microaerophilic nature of the bacterium, C. jejuni can survive the atmospheric oxygen conditions in the environment. Bacteria that can survive either within a host or in the environment like C. jejuni require variable responses to survive the stresses associated with exposure to different levels of reactive oxygen species. The MarR-type transcriptional regulators RrpA and RrpB have recently been shown to play a role in controlling both the C. jejuni oxidative and aerobic stress responses. Analysis of 3,746 Campylobacter jejuni and 486 Campylobacter coli genome sequences showed that whilst rrpA is present in over 99% of C. jejuni strains, the presence of rrpB is restricted and appears to correlate with specific MLST clonal complexes (predominantly ST-21 and ST-61). C. coli strains in contrast lack both rrpA and rrpB. In C. jejuni rrpB+ strains, the rrpB gene is located within a variable genomic region containing the IF subtype of the type I Restriction-Modification (hsd) system, whilst this variable genomic region in C. jejuni rrpB- strains contains the IAB subtype hsd system and not the rrpB gene. C. jejuni rrpB- strains exhibit greater resistance to peroxide and aerobic stress than C. jejuni rrpB+ strains. Inactivation of rrpA resulted in increased sensitivity to peroxide stress in rrpB+ strains, but not in rrpB- strains. Mutation of rrpA resulted in reduced killing of Galleria mellonella larvae and enhanced biofilm formation independent of rrpB status. The oxidative and aerobic stress responses of rrpB- and rrpB+ strains suggest adaptation of C. jejuni within different hosts and niches that can be linked to specific MLST clonal complexes.